Cubosomes: remarkable drug delivery potential. Issue 5 (May 2016) - Karami, Zahra; Hamidi, Mehrdad
Graphical abstract: Highlights: Cubosomes are among the recent nanostructures attracting attention for drug delivery. Biocompatibility and simplicity are the most important advantages of cubosomes. The most-used materials in the fabrication of cubosomes are amphiphilic lipids. Different types of drugs have been delivered using cubosomes. Abstract : Cubosomes are nanostructured liquid crystalline particles, made of certain amphiphilic lipids in definite proportions, known as biocompatible carriers in drug delivery. Cubosomes comprise curved bicontinuous lipid bilayers that are organized in three dimensions as honeycombed structures and divided into two internal aqueous channels that can be exploited by various bioactive ingredients, such as chemical drugs, peptides and proteins. Owing to unique properties such as thermodynamic stability, bioadhesion, the ability of encapsulating hydrophilic, hydrophobic and amphiphilic substances, and the potential for controlled release through functionalization, cubosomes are regarded as promising vehicles for different routes of administration. Based on the most recent reports, this review introduces cubosomes focusing on their structure, preparation methods, mechanism of release and potential routes of administration. Teaser: Cubosomes are among the most promising drug delivery systems of the future owing to their remarkable unique multicompartmental structure and the possibility of being loaded by a wide variety of drugs, most importantly proteins and peptides.